Improving The Use of Blockchain Technology in The Finance of Economic Entities - Kamalov Shukhrat Kamalovich (Peerian Journals Publishing, 2023)
The article describes the analysis of the current situation of using blockchain technology in the finance of economic entities, in particular, in banking and finance, insurance, state administration, industrial enterprises, in the process of accounting for intellectual property, and in the implementation of the contract system of producers and users. In addition, the use of blockchain technology in smart corporate financial management, the use of IoT, Cloud technologies, blockchain technology in drawing up smart contracts was developed. A comparative analysis of blockchain technology evaluation methods was performed
Keywords: Blockchain; digitization; smart contract; cloud